PENGARUH WAKTU PEMASAKAN DAN KONSENTRASI ALKALI AKTIF TERHADAP RENDEMEN DAN SIFAT FISIK PULP KAYU BUSH PUTIH (Melaleuca viridiflora) MELALUI PROSES SULFAT - , RINA AFIANI REBIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Melaleuca viridiflora ) In order to obtain alternative raw material for pulp, a study has been conducted by using bush putih wood ( through sulphate process with factors of alkali active concentration and short cooking period. The material of this study was bush putih wood which obtained from Zanegi block as the area owned by PT. Selaras Inti Semesta and PT. MIL (Medcopapua Industri Lestari) in Merauka Papua. Research used Completely Randomized Design with two different factors and three replications. The first factor was alkali active concentration through 14% and 16% of concentration while the second factor was comprised by 60, 90, and 120 minutes of cooking period. Result showed that bush putih wood was suitable to be used as pulp material with sulphate process as it performed value range 35.43%-45.64% of yield, 25.84-30.70 of kappa number, 30.22-39.92Nm/g of tensile index, 1.46-1.8 KPa.m 2 /g of bursting strength and 3.05-5.43 mNm 2 /g of tear strength. The alkali active concentration gave influence to the yield while the cooking period gave influence to the bursting and tear strength. In addition, the alkali active concentration gave significant influence to the tear strength.